2011
DOI: 10.1007/s11144-011-0370-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of reaction mechanisms and kinetics of preferential CO oxidation over Au/γ-Al2O3

Abstract: In this work, the mechanism and kinetics of the preferential CO oxidation over 0.5 wt. % Au/Al 2 O 3 catalyst was investigated. For CO oxidation, the reaction was found to follow a two-step Eley-Rideal-type mechanism, in which the formation and decomposition of the reaction intermediate took place at the gold-support interface. For the PROX case, on the other hand, Langmuir-Hinshelwood-type mechanisms seem to be also significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…As concerns the kinetics, several models have been proposed for the PROX reaction over CuO xCeO 2 [25][26][27][28][29][30][31][32]. The formulation of adequate kinetic models is a key step on designing and scaling up of PROX units [33], thus being fundamental for the practical applications of this H 2 cleaning technology.…”
Section:  mentioning
confidence: 99%
“…As concerns the kinetics, several models have been proposed for the PROX reaction over CuO xCeO 2 [25][26][27][28][29][30][31][32]. The formulation of adequate kinetic models is a key step on designing and scaling up of PROX units [33], thus being fundamental for the practical applications of this H 2 cleaning technology.…”
Section:  mentioning
confidence: 99%
“…Concerning the kinetics of the Cu/CuO-CeO 2 [33][34][35][36][37] and Aucatalyzed [38][39][40][41][42][43][44] CO-PROX reactions, it has been shown that copper-catalyzed reactions exhibited high values of apparent activation energies (Ea), from 50 to 100 kJ/mol, whereas goldcatalyzed reactions exhibited much lower Ea with values of 20-40 kJ/mol. Besides, for supported Au catalysts, the partial reaction orders of both CO (a) and O 2 (b) for supported Au are positive.…”
Section: Introductionmentioning
confidence: 99%
“…[29] The presence of H 2 in the feed usually enhanced the CO conversion, even though it sometimes negatively affected the selectivity (which is not a serious problem for this system as explained in the Introduction). [30] Although the presence and absence of H 2 made some difference in the catalytic activity, the change in H 2 concentration did not significantly affect CO conversion because H 2 was almost always in excess when present.…”
Section: Review Of Publications From 2000 To 2012mentioning
confidence: 94%